Effects of explicit instruction of intertextual integration on the reading comprehensive skills of struggling adolescent readers - Abug, Abigael T.
This mixed-methods case study explored the effects of explicit instruction in intertextual integration on the reading comprehension skills of struggling adolescent readers in a public high school in Manila. Focusing on Grade 9 students, the study addressed (a) the effectiveness of explicit instruction on comprehension performance, (b) the extent to which intertextual integration was applied, and © the role of explicit instruction in developing comprehension skills.